Injecting-related injury and disease among clients of a supervised injecting facility - Salmon, A.; Dwyer, Robyn; Jauncey, M.; van Beek, I.; Topp, L.; Maher, L. (Elsevier Ireland Ltd, 2009)
Background: The process of drug injection may give rise to vascular and soft tissue injuries and infections. The social and physical environments in which drugs are injected play a significant role in these and other morbidities. Supervised injecting facilities (SIFs) seek to address such issues associated with public injecting drug use. Aims: Estimate lifetime prevalence of injecting-related problems, injury and disease and explore the socio-demographic and behavioral characteristics associated with the more serious complications. Design, Setting, Participants: Self-report data from 9552 injecting drug users (IDUs) registering to use the Sydney Medically Supervised Injecting Centre (MSIC). Findings: Lifetime history of either injecting-related problems (IRP) or injecting-related injury and disease (IRID) was reported by 29% of the 9552 IDUs; 26% (n = 2469) reported ever experiencing IRP and 10% (n = 972) reported IRID. Prevalence of IRP included difficulties finding a vein (18%), prominent scarring or bruising (14%) and swelling of hands or feet (7%). Prevalence of IRID included abscesses or skin infection (6%), thrombosis (4%), septicaemia (2%) and endocarditis (1%). Females, those who mainly injected drugs other than heroin, and those who reported a history of drug treatment, drug overdose, and/or sex work, were more likely to report lifetime IRID. Frequency and duration of injecting, recent public injecting, and sharing of needles and/or syringes were also independently associated with IRID. Conclusions: IRPs and IRIDs were common. Findings support the imperative for education and prevention activities to reduce the severity and burden of these preventable injecting outcomes. Through provision of hygienic environments and advice on venous access, safer injecting techniques and wound care, SIFs have the potential to address a number of risk factors for IRID. © 2009 Elsevier Ireland Ltd. All rights reserved.